Compendium of Climate-Resilient Agriculture Technologies and Approaches in the Philippines - Labios, Romeo V; Sebastian, Leocadio S.; Labios, Jocelyn D; Santos, Christine Mae B (2019)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), together with the Department of Agriculture (DA), the Philippine Council for Agriculture, Aquatic and Natural Resources Research and Development (PCAARRD), and the Southeast Asian Regional Center for Graduate Study and Research in Agriculture (SEARCA), developed the Compendium of Climate-Resilient Agriculture Technologies and Approaches in the Philippines. CCAFS SEA worked with various agricultural experts in the Philippines to list climate-resilient agriculture (CRA) options that Filipino farmers can adopt on their farms. The CRA options discussed in this Compendium are grouped based on their suitability for the different agro-ecological landscapes in the Philippines. The CRA options not only improve the agricultural productivity of farmers; they also enhance the farmers’ adaptive capacity against climate change impacts and reduce the greenhouse gas emissions from their farming activities. The Compendium mentions different activities that can promote and disseminate these CRA options in the Philippines. Alongside the activities, it identifies various strategies to help the country overcome the challenges in applying and scaling these options.